(untitled) (Journal of Scientific Research, 2016)
The effect of annealing temperatures on the surface morphology and optical properties of titanium dioxide (TiO2) thin films deposited by spin coating on Silicon substrate was studied. The TiO2 thin films deposited onto silicon substrates were annealed at different temperatures. The structural and optical properties were studied using scanning electron microscopy (SEM), X-ray diffraction technique (XRD) and optical ellipsometer. The results indicated that the structural properties of the TiO2 thin films were changed with the increase in annealing temperature. The SEM investigation showed that as annealing temperature was increased, the grain and pores size were increased. The XRD patterns of the studied samples showed that rutile phase were found in a sample annealed at high temperature. The ellipsometry investigation shows that the refractive index increased while energy band gap decreased with the annealing temperature. The results showed that surface porosity, optical properties and surface morphology of TiO2 could be affected by changing the annealing temperature.